TINJAUAN HUKUM ISLAM TENTANG PENGENAAN NILAI KEWAJIBAN ZAKAT ATAS KEPEMILIKAN OBLIGASI NEGARA - NIM. A1012211027, MUHAMMAD ZAINI RAHMAN (Jurnal Fatwa Hukum, 2025)
Abstract Government Bonds are securities in the form of debt recognition, these securities can be traded and will be bought back by the state with the same value when purchased in the primary/secondary market. There are various views regarding the imposition of zakat obligations on bonds, in general zakat on bonds is analogous to trade zakat, but in the imposition of trade zakat it is important to have the intention that the assets purchased will be sold in the future. We realize that not everyone who buys bonds intends to sell them, because there are coupons that are the source of profit from ownership of the bonds. Thus, the application of zakat obligations on bonds only analogous to trade zakat is not entirely correct. The type of research in this study is Normative Juridical. The nature of the research in this study is Descriptive. The type of approach in this study is Conceptual Approach and Legislation Approach. The types of data in this study are Primary Data, Secondary Data, and Tertiary Data. The method of data collection in this study is through Literature Study and Interviews with informants. Data analysis in this study is through Qualitative data analysis. The imposition of the zakat obligation value on government bonds depends on the owner's intention when purchasing it. If it is intended to be sold later, it is analogous to trade zakat, and if it is intended only to be stored or without any intention, it is analogous to savings zakat. Keywords: Intention, Zakat, and Government Bonds. Abstrak Obligasi Negara merupakan surat berharga berupan pengakuan hutang, surat berharga tersebut dapat diperjual belikan serta akan dibeli kembali oleh negara dengan nilai yang sama pada saat dibeli di pasar perdana/sekunder. Terdapat berbagai pandangan yang berkenaan dengan pengenaan nilai kewajiban zakat atas obligasi, secara umum zakat obligasi dianalogikan kedalam zakat perdagangan, namun dalam pengenaan zakat perdagangan penting adanya niat bahwa harta yang dibeli akan dijual dikemudian hari. Kita menyadari bahwa tidak semua orang yang membeli obligasi berniat untuk menjualnya, dikarenakan terdapat kupon yang menjadi sumber keuntungan dari kepemilikan obligasi tersebut. Dengan demikian penerapan kewajiban zakat atas obligasi hanya dianalogikan dengan zakat perdagangan tidaklah sepenuhnya tepat. Jenis penelitian dalam penelitian ini adalah Yuridis Normatif. Sifat penelitian dalam penelitian ini yaitu Deskriptif. Jenis pendekatan dalam penelitian ini adalah Pendekatan Konseptual dan Pendekatan Perundang-Undangan. Jenis data dalam penelitian ini yaitu Data Primer, Data Sekunder, dan Data Tersier. Cara pengumpulan data dalam penelitian adalah dengan Studi Kepustakaan dan Wawancara kepada informan. Analisis data dalam penelitian ini yaitu dengan analisis data Kualitatif. Pengenaan nilai kewajiban zakat atas obligasi negara tergantung pada niat pemilik ketika membelinya. Jika diniatkan untuk dijual dikemudian hari maka dianalogikan kedalam zakat perdagangan, dan jika diniatkan hanya untuk disimpan atau tanpa diniatkan maka dianalogikan kedalam zakat simpanan. Kata Kunci: Niat, Zakat, Obligasi Negara.